2020
DOI: 10.3390/nano10040785
|View full text |Cite
|
Sign up to set email alerts
|

Discriminable Sensing Response Behavior to Homogeneous Gases Based on n-ZnO/p-NiO Composites

Abstract: Metal oxide semiconductor (MOS) gas sensors have the advantages of high sensitivity, short response-recovery time and long-term stability. However, the shortcoming of poor discriminability of homogeneous gases limits their applications in gas sensors. It is well-known that the MOS materials have similar gas sensing responses to homogeneous gases such as CO and H2, so it is difficult for these gas sensors to distinguish the two gases. In this paper, simple sol–gel method was employed to obtain the ZnO–xNiO comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 63 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…It is found that selectivity can be regulated by the modulation of barrier height in heterojunction through the asymmetric gas sensing reactivity of heteromaterials. 48,273 Hu et al 48 Heterostructure can significantly improve the sensor performance and reduce the detection limit of the sensor due to its extremely high chemical reaction activity as well as the presence of a large number of oxygen vacancies at the interface. Scientific researchers can also achieve excellent selective sensor preparation by adjusting the barrier height of heterostructures, but much progress is still needed to reduce the working temperature of gas sensor.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…It is found that selectivity can be regulated by the modulation of barrier height in heterojunction through the asymmetric gas sensing reactivity of heteromaterials. 48,273 Hu et al 48 Heterostructure can significantly improve the sensor performance and reduce the detection limit of the sensor due to its extremely high chemical reaction activity as well as the presence of a large number of oxygen vacancies at the interface. Scientific researchers can also achieve excellent selective sensor preparation by adjusting the barrier height of heterostructures, but much progress is still needed to reduce the working temperature of gas sensor.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Several studies have worked on the improvement for selectivity [ 12 , 13 , 14 ] and electrical property [ 15 , 16 ] of MOS gas sensors. The reliability and limitation issues have also been solved by application of composite material [ 17 , 18 , 19 ]. The resistance of a sensor varies with both the nature of the surrounding gases and their concentration [ 20 ], which can be evaluated by measuring the voltage of the sensors.…”
Section: Distinguishing the Samples At Various Stagesmentioning
confidence: 99%
“…Concerning its morphology, ZnO has been obtained as nanostructures, which include nanoneedles, nanosticks, nanocouples, nanoflakes, nanosprings, nanotubes, nanorods, and nanowires [ 31 , 34 , 35 ], as well as porous and dense films [ 36 ]; as gas sensing performance is mainly dependent on the morphology of the material. Significant achievements have been attained in the fabrication of gas sensors based on ZnO structures, including biosensors [ 16 , 30 , 36 , 37 , 38 , 39 , 40 , 41 ]. Nevertheless, further research is needed to improve CO detection at low operating temperatures (e.g., room temperature) and with excellent selectivity to differentiate two gases with similar behaviors, considering the effect of the relative humidity on the gas sensing performance [ 38 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant achievements have been attained in the fabrication of gas sensors based on ZnO structures, including biosensors [ 16 , 30 , 36 , 37 , 38 , 39 , 40 , 41 ]. Nevertheless, further research is needed to improve CO detection at low operating temperatures (e.g., room temperature) and with excellent selectivity to differentiate two gases with similar behaviors, considering the effect of the relative humidity on the gas sensing performance [ 38 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%